Fronteiras de um quilombo em construção : um estudo sobre o processo de demarcação das terras da Comunidade Negra Manoel Ciríaco dos Santos Guairá/PR. - Hoffmann, Claudia Cristina (2012)
The present study examined experiences of the Black Community Manoel Ciríaco dos Santos, located in Maracaju dos Gauchos, Guaíra, PR. This community is involved in a process of identifying the remaining quilombola community and demarcation of land, in a context of public policies to promote racial equality, appreciation of blacks and quilombolas (maroons) in Brazil and in the state of Paraná. The text was written based on interviews, community visits, data collection and data sources such as documents, photographs and memories recorded on the community. The processes of demarcation of Quilombola lands in Brazil occur after the interest and request of community members who have this goal, to the Palmares Cultural Foundation (PCF), citing signs of africanities, features of traditional community and self recognition of remnant quilombo, based on Federal Decree 4887-2003 and practiced by the National Institute of Colonization and Agrarian Reform (INCRA). From the interest of members of the black community Manoel Ciríaco dos Santos to be remnant quilombo, historical, identity, cultural and spatial changes were perceived and these changes affected their daily lives. Among the major changes it s possible to highlight conflicts and different interests in face of territorial and border changes. Accordingly, the multiple boundaries related to the territory of the black community in question were analyzed, because these are fluid and go beyond the visible boundaries such as fences, walls or documents. They are boundaries between groups, individuals, institutions and ideological positions that indicate tension and reveal the dynamics of living in community and society.